A novel route to fabricate Yb:YAG ceramic fiber and its optical performance. Issue 8 (July 2021) - Gao, Pan; Zhang, Le; Yao, Qing; Ma, Yuelong; Shao, Cen; Zhou, Tianyuan; Liu, Mingyuan; Zhu, Lv; Chen, Hao; Cheng, Xin; Yang, Hao
Highlights: A novel aqueous gelcasting route to prepare Yb:YAG transparent ceramic fiber. A high solid loading and low viscosity into the capillary glass tube. A green fiber without cracks and deformation. A diameter of 1.0 mm and a length of 43.0 mm for 15.0 at.% Yb:YAG ceramic fiber. Abstract: Transparent laser ceramics are the attractive gain medium for solid-state lasers. However, they have not been applied to the fiber lasers due to the difficulty of forming green fibers by traditional methods. In this study, a novel route combined aqueous gelcasting with capillary glass tube was designed to prepare Yb:YAG transparent ceramic fiber with a diameter of 1.0 mm and 43.0 mm in length for the first time. The slurry with high solid loading and low viscosity was smartly inhaled into the capillary glass tube to conquer the difficulty of casting. The green fibers without cracks and deformation had highly dense microstructure. The in-line transmittance of highly doped 15.0 at.% Yb:YAG transparent ceramic disc prepared from the same preparation conditions of Yb:YAG ceramic fiber was 80.0 % at 1064 nm. This study provides a novel route to prepare transparent ceramic fiber differing from extrusion processing, promoting the development of fiber laser.